9(9+-4)=12(12t-3)

Simple and best practice solution for 9(9+-4)=12(12t-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(9+-4)=12(12t-3) equation:


Simplifying
9(9 + -4) = 12(12t + -3)

Combine like terms: 9 + -4 = 5
9(5) = 12(12t + -3)

Multiply 9 * 5
45 = 12(12t + -3)

Reorder the terms:
45 = 12(-3 + 12t)
45 = (-3 * 12 + 12t * 12)
45 = (-36 + 144t)

Solving
45 = -36 + 144t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-144t' to each side of the equation.
45 + -144t = -36 + 144t + -144t

Combine like terms: 144t + -144t = 0
45 + -144t = -36 + 0
45 + -144t = -36

Add '-45' to each side of the equation.
45 + -45 + -144t = -36 + -45

Combine like terms: 45 + -45 = 0
0 + -144t = -36 + -45
-144t = -36 + -45

Combine like terms: -36 + -45 = -81
-144t = -81

Divide each side by '-144'.
t = 0.5625

Simplifying
t = 0.5625

See similar equations:

| 6x+x-12=468 | | 4y-12=y^2 | | (2x-1)(5x+1)= | | 3x-15+6x+8=15 | | 3x^2+2x^2=117 | | x*0.2=25 | | 5p+2q=3p-3q | | 7j+14=98 | | (3x)2+(2x)2=117 | | 5t-4=3f+6 | | 6(k+8)=90 | | 2(w+11)=40 | | 10(u+7)=80 | | x^2-2x-16=x^2 | | 0=-3x^2+24x-36 | | 6(g-91)=6 | | 3q+21=72 | | 2+6u=44 | | 6=167+21 | | 2x+-2=11x-38 | | (x+2)(x+3)=(3x+4)(x+3) | | 1.1x*0.583=0.2 | | 10y+13x+200=1500 | | 25=4y+29 | | x-3(2x+8)=-3 | | 0.2=x+(x-0.1)*0.583 | | x-6x+8=-3 | | 4(3x-y)=40 | | 5(2x-3)=2(5x+3) | | 6(x+2)=2x+2(x+1) | | 4x-(3-5x)=87 | | .65x=5 |

Equations solver categories